Prediction of mental health among university students - Sahlan, Fadhluddin; Hamidi, Faris; Misrat, Muhammad Zulhafizal; Adli, Muhammad Haziq; Wani, Sharyar; Gulzar, Yonis (IIUM Press, 2021)
Mental Illness or mental disorder is defined as a health condition that changes a person’s thinking, feelings, or behaviour which can cause the person to distress and face difficulty to live normally. Unlike other diseases, mental illness doesn’t only harm the affected individual, but also others around them. Early detection of mental disorders can help to avoid severe consequences. Mental wellness issues have been largely reported in university students. This paper explores the state of student well-being and uses various machine learning algorithms for the prediction process based on the data of entrepreneurial competency in university students. The results indicate the choice of major and gender has a significant impact on a student’s well-being. Decision Tress perform better than KNN and SVM presenting an accuracy and F1-score of 0.64 and 0.61 respectively